Smart Screening: Using The hearWHO App to Assess Hearing Health in South Indian Medical Students Using Personal Listening Devices (PLDs) - Ritikaa S; Vijayakarthikeyan M; Eldho, Sara; Sangeetha S (National Journal of Community Medicine, 2026)
Background: Hearing loss represents a significant global public health challenge, with young individuals increasingly at risk due to preventable causes such as unsafe listening practices. This study aims to estimate the prevalence of likely hearing impairment among medical students who use personal listening devices and to identify the factors associated with this impairment. Materials and Methods: 650 medical students from a tertiary care hospital in South India participated in this cross-sectional analytical study. Data was gathered using a semi-structured questionnaire and hearWHO application was employed to screen participants for likely hearing impairment based on their test score. Data analysis was done using SPSS Software Version 22. Results: About 56.5% of students used PLDs for educational purposes and 85.5% use Bluetooth earphones. Overall based on hearWHO app screening, 26.1% were likely to have some degree of hearing impairment and 49.4% need screening regularly for hearing impairment. Family history of hearing problems, prolonged PLD use, high-volume listening and lack of breaks during prolonged use were significantly associated with likely hearing impairment. Conclusion: Educational programs should be developed to raise awareness on the effects of noise-induced hearing loss. Students with high-risk behaviors identified in this study must be targeted for such programs.